Metastatic triple-negative breast cancer successfully treated with bicalutamide - Salazar Mejía, Carlos Eduardo; García Gutierrez, María Elena; Rodríguez Alvarez, Carlos Javier; Flores Caballero, Miguel Angel; Wimer Castillo, Blanca Otilia; Vidal Gutiérrez, Oscar (African Field Epidemiology Network, 2020)
Triple-negative breast cancer (TNBC) is considered the group with the worst prognosis among the four molecular subtypes of breast cancer. The current treatment of metastatic TNBC is traditionally limited to chemotherapy. Androgenic receptors (AR) are an emerging target with therapeutic potential in TNBC refractory to chemotherapy. We present the case of a 66-year-old woman diagnosed with TNBC who had failed to 2 lines of chemotherapy after a diagnosis of recurrence. Immunohistochemistry was requested for the determination of AR, which was positive without specifying the percentage of AR expression. We started bicalutamide 50 mg QD, achieving disease control. At 50 months from the start of this treatment, the patient remains in stable disease, without any toxicity associated with treatment. Androgenic blockade could represent another management option for patients with advanced TNBC. The drug of choice and the dose to be used in this setting remains controversial. Furthermore, there is no consensus on the percentage of tumoral expression of AR to be considered a candidate for this treatment.